Evaluation of psychological empowerment of academics in innovative pedagogical delivery: the role of inclusive leadership and achievement orientation - Vem, Linus Jonathan; Ng, Siew Imm; Sambasivan, Murali; Maimako, Sabastian Seddi (Emerald Publishing, 2024)
Purpose: Innovative pedagogical delivery (IPD) and behaviour have been a major concern among academics in Nigeria. The purpose of this study is aimed at analyzing the impact of psychological empowerment (PE) on IPD through achievement orientation (AO) and perceived inclusive leadership (PIL) among academics of tertiary institutions in Nigeria. Design/methodology/approach: A questionnaire-based survey was conducted among the academics in Nigeria, and 350 responses were received. A multiple regression analysis was conducted using Smart-PLS version 3. Findings: Findings are: (a) PE significantly impacts AO and IPD; (b) AO mediates the relationship between PE and IPD; and (c) PIL moderates the relationship between PE and AO. Practical implications: It is recommended that practitioners and administrators in tertiary institutions pay attention to academics’ AO while integrating employee empowerment intervention for optimum results. Originality/value: The findings emphasize AO in explaining the mechanism by which the relationship between PE and IPD holds sway. PIL explains the boundary conditions under which PE can effectively influence IPD. © 2023, Emerald Publishing Limited.